Physiological and performance effects of carbohydrate gels consumed prior to the extra-time period of prolonged simulated soccer match-play - Harper, L. D.; Briggs, M. A.; McNamee, G.; West, D. J.; Kilduff, L. P.; Stevenson, E.; Russell, M. (Journal of Science and Medicine in Sport, 2016)
Objectives: The physiological and performance effects of carbohydrate-electrolyte gels consumed before the 30 min extra-time period of prolonged soccer-specific exercise were investigated. Design: Randomised, double-blind, crossover. Methods: Eight English Premier League academy soccer players performed 120 min of soccer-specific exercise on two occasions while consuming fluid-electrolyte beverages before exercise, at half-time and 90 min. Carbohydrate¨Celectrolyte (0.7+/-0.1 g kg.1 BM) or energy-free placebo gels were consumed ~5 min before extra-time. Blood samples were taken before exercise, at half-time and every 15 min during exercise. Physical (15-m and 30-m sprint speed, 30-m sprint maintenance and countermovement jump height) and technical (soccer dribbling) performance was assessed throughout each trial. Results: Carbohydrate¨Celectrolyte gels improved dribbling precision (+29+/- 20%) and raised blood glucose concentrations by 0.7+/-0.8 mmol l.1 during extra-time (both p < 0.01). Supplementation did not affect sprint velocities (15 m and 30 m), 30-m sprint maintenance or dribbling speed as reductions compared to 0¨C15 min values occurred at 105¨C120 min irrespective of trial (all p < 0.05). Plasma osmolality and blood sodium concentrations increased post-exercise vs. the opening 15 min (p < 0.05) but no effect of supplementation existed. Selected markers of physical performance (jump height, 30-m sprint velocity and 30-m repeated sprint maintenance) also reduced by >3% during half-time (all p < 0.05). Conclusions: Carbohydrate¨Celectrolyte gel ingestion raised blood glucose concentrations and improved dribbling performance during the extra-time period of simulated soccer match-play. Supplementation did not attenuate reductions in physical performance and hydration status that occurred during extratime.